Lender of last resort and the moral hazard problem - Mikko Niskanen (Bank of Finland, 2002)
We study the effects of investor protection on the availability of external finance, entrepreneurship, and creation of new firms in an equilibrium search model of private capital markets.In addition to search frictions, we examine contract frictions, specifically interim and ex post moral hazard problems stemming from entrepreneurs' possibilities to expropriate financiers.In our model, the government chooses the level of investor protection that determines the transferability of match surplus between entrepreneurs and financiers.The results indicate that anything that increases (decreases) entrepreneurship also increases (decreases) the creation of start-ups.The effect of investor protection on the creation of start-ups thus hinges on the relative importance of various search and contract frictions.Only when investor protection has a sufficiently large impact on the ex post moral hazard problem relative to the interim moral hazard does strengthening investor protection enhance start-up creation.We also find that search frictions dilute the beneficial effect of investor protection and that contract frictions modify the standard Hosios condition for efficiency.
URN:NBN:fi:bof-20140807422
Keywords: E50; G21; G24; 330; investor protection; start-up financing; private equity market; entrepreneurship; corporate finance